2020
DOI: 10.1007/s12144-020-00635-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, social and biological correlates of body perception disturbance in complex regional pain syndrome

Abstract: Body Perception Disturbance (BPD) in Complex Regional Pain Syndrome (CRPS) still represents a poorly understood phenomenon. Research has shown that knowledge about changes in body perception can yield relevant information for understanding and treating the disease. This study addressed possible connections between BPD and psychological and social factors, pain intensity, and disease duration. Sixty patients with chronic CRPS Type I of the hand were recruited. Body Perception Disturbance was assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Mixed results have been reported regarding the relationships between body perception disturbance as measured with the B-CRPS-BPDS and disease characteristics in people with CRPS. Positive relationships between body perception disturbance and pain intensity have been found in some studies, 32,51 but not others. 57 One study found positive relationships between body perception disturbances and depression, anxiety, stress, and quality of life.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Mixed results have been reported regarding the relationships between body perception disturbance as measured with the B-CRPS-BPDS and disease characteristics in people with CRPS. Positive relationships between body perception disturbance and pain intensity have been found in some studies, 32,51 but not others. 57 One study found positive relationships between body perception disturbances and depression, anxiety, stress, and quality of life.…”
Section: Introductionmentioning
confidence: 89%
“…1,32 Several studies have evaluated the construct validity of the B-CRPS-BPDS. With regard to other measures that have been related to body perception disturbances, 20,51 B-CRPS-BPDS scores were associated with worse tactile acuity and higher scores on the neurobehavioral questionnaire. 32,36 However, a study using a French translation of the B-CRPS-BPDS (N=13; including fewer items than the original) found no relationship between B-CRPS-BPDS scores and the senses of limb position and movement.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Depression, anxiety and current stress have also been found to be associated with body perception disturbance [51]. Subsequent disengagement and disuse of the affected limb, commonly seen in CRPS [48,52], are thought to be contributing and maintaining factors to the condition and which may lead to cortical changes [53].…”
Section: Psychological Therapymentioning
confidence: 99%